A inovação como diferencial para o segmento alta renda: estudo de caso em uma instituição financeira - Marques, Fábio Henrique Antonio (2018)
The aim of this study was to analyze the effectiveness of the digital service platform meant for clients with high income profile of the studied Bank. The specific objectives were to measure the financial return of the new digital business model; to evaluate the feedback of the institutional image; to evaluate the clients’ level of satisfaction with the digital platform, and to search for improvement suggestions in partnership with the clients. This Case Study analyzes the technological innovation in the segment of clients with high income profile in a Brazilian Financial Institution. New technologies, especially the ones related to instant messaging which are available in smartphone’s apps, innovated the manners to approach clients, and also brought the need of greater investments by banks. Currently, it is possible to notice the increase of customer preference for alternative service schedules, for messaging with the bank e for a greater interaction in digital channels. No correlated studies were found in banks of national financial system. The theme “innovation” appears in a substantial part of the literature review, being referenced through several authors and aspects, including the innovation in bank services. Christensen (2012) is a seminal researcher in innovation area, and his contributions are valuable to this study. In terms of methodological procedures, the study is organized in a qualitative approach, with descriptive and exploratory goals, using document analysis technique conducted by Case Study. To data collecting, semi-structured interviews were made with 44 clients of the Financial Institution, and content analysis was used to process the data of this research. It was possible to verify that the financial return of the digital platform model was superior when compared to the traditional model of service, since it was verified an average growth of 26.40% in profitability of high income profile clients in national terms, and 34.61% in the specific bank branch. The second objective, which aimed at measuring the feedback of the institutional image, was also met since it was verified that there were 41 mentions of the Sigma Bank being secure, reliable and solid. In terms of clients’ satisfaction, the answers of the participants showed the inexistence of unsatisfied clients, besides the important number of 33 clients, among the 44 interviewed, who are completely satisfied. The final part of the interview allowed the client to express his suggestion for digital platform improvement. It is considered, then, that the main objective of this study, which was to analyze the effectiveness of digital platform to high income profile clients of Sigma Bank, was reached and can be synthesized as having good efficacy. Finally, it is not recommended to generalize the results of this Case Study; however, the provocation presented in this research can be a point of departure and continuity in other studies in the area.